Hepatoprotective Effect of Parijoto Fruit Extract (Medinilla speciosa Blume) on Male Mice Fed with High-Fat Diet - Nabila, Inasa; Thadeus, Maria Selvester; Herardi, Ryan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aims to determine the effectiveness of parijoto fruit extract (Medinilla speciosa Blume) in improving the condition of fatty liver in male balb/c mice (Mus musculus L.) fed with a high-fat diet. Thirty male balb/c mice weighing 20 to 30 g were randomly divided into six groups, i.e: 1) Standard feed and Carboxymethyl Cellulose Sodium or CMC-Na 0.5% (K1); 2) High-fat diet and CMC-Na 0.5% (K2); 3) High-fat diet and simvastatin 0.026 mg/day (K3); 4) High-fat diet and parijoto fruit extract 5.6 mg/20 g BW (P1); 5) High-fat diet and parijoto fruit extract 8.4 mg/20 g BW (P2); 6) High-fat diet and parijoto fruit extract 11.2 mg/20 g BW (P3). Standard feed, high-fat diet, simvastatin, and parijoto fruit extract were administered for 56 days. On the 57th day, the total of 30 mice were terminated and the livers were then removed for H&E staining histopathological slides. Data on the degree of fatty liver on histopathological slides were collected and analyzed using the Kruskal-Wallis test and followed by the Mann-Whitney test. The histopathological analysis showed Medinilla speciosa Blume extract at a dose of 5.6 mg/20 g BW in group P1 prevent the steatosis degree compared to high-fat feed mice in group K2 (p>0.05). Parijoto fruit extract could act as the potential treatment for fatty liver.